Photobleaching-induced changes in photosensitizing properties of dissolved organic matter - Niu, X.; Liu, C.; Gutierrez, L.; Croué, Jean-Philippe (IWA Publishing, 2014)
Photosensitizing properties of different dissolved organic matter (DOM) were investigated according to their performance in singlet oxygen (1O2), triplet state of DOM (3DOM*), and hydroxyl radical (·OH) productions. The photobleaching of DOM solutions after irradiation was characterized by fluorescence excitation-emission matrix and UV-Vis spectroscopy. The photosensitizing properties of pre-irradiated DOM solutions were changed in a sunlight simulator. The performance of DOMs in photosensitized degradation of several contaminants was investigated. For a 20h exposure, the observed degradation rate constant (kobs) of some contaminants decreased as a function of exposure time, and highly depended on the properties of both DOM and contaminant. Degradation of contaminants with lower kobs was more susceptible to DOM photobleaching-induced decrease in kobs. Under the current experimental conditions, the photobleaching-induced decrease of DOM photo-reactivity in contaminant degradation was mainly attributed to indirect phototransformation of DOM caused by the interactions between photo-inductive DOM moieties and photochemically-produced reactive species. Reactive contaminants can inhibit DOM indirect photobleaching by scavenging reactive species, photosensitized degradation of these contaminants exhibited a stable kobs as a result. This is the first study to report DOM photobleaching-induced changes in the simultaneous DOM photosensitized degradation of contaminants and the inhibitory effect of reactive contaminants on DOM photobleaching.